Clinical Characteristics of Hospitalized Neonates With Hypofibrinogenemia: A Retrospective Cohort Study - Zhou, Weijun; He, Yichun; Li, Qin; Li, Ying; Su, Yongchun; Yan, Li (Frontiers in Pediatrics, 2020)
Background: Neonatal hypofibrinogenemia is often asymptomatic but can manifest as hemorrhage. Objective: To characterize clinical characteristics of neonates with hypofibrinogenemia and identify factors associated with hemorrhage. Methods: This was a retrospective study of neonates with plasma fibrinogen level (FIB) ≤1.0 g/L who were hospitalized at the Neonatology Department, People’s Hospital, Chongqing, China, from January 2012 to December 2017. Based on severity, patients were grouped into severe, moderate, and mild hypofibrinogenemia (FIB <0.5 g/L, 0.5 g/L ≤ FIB < 0.7 g/L, and 0.7 g/L ≤ FIB ≤ 1.0 g/L, respectively). Clinical characteristics associated with hemorrhage were analyzed. Results: Among 330 neonates, 52.7% showed mild hypofibrinogenemia, 25.5% had moderate hypofibrinogenemia, and 21.8% had severe hypofibrinogenemia. Severe hypofibrinogenemia was not associated with gestational age, but the mild form was frequent in neonates with low/normal birthweight (P = 0.018). Approximately 80.6% of neonates presented hypofibrinogenemia as variable combinations of thrombocytopenia or coagulopathies. Hemorrhage occurred in 38.8% of cases, 60.9% of which were mild. Hemorrhage manifested as puncture site bleeding (47.7%) or spontaneous skin/mucous membrane bleeding (34.2%). Degree of hypofibrinogenemia was not associated with the severity or occurrence of hemorrhage. Among patients with hypofibrinogenemia and bleeding, 53.4% of cases with coagulopathies showed mild hemorrhage, 85.7% of cases with thrombocytopenia had moderate bleeding, while 53.8% of cases with coagulopathy and thrombocytopenia showed severe hemorrhage. Conclusion: Neonatal hypofibrinogenemia is often comorbid and occurs with thrombocytopenia and/or coagulopathies. Although hemorrhage is not associated with the degree of hypofibrinogenemia, it may be severe when hypofibrinogenemia co-occurs with coagulopathies and/or thrombocytopenia.